2015
DOI: 10.1039/c5dt00372e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic colloidal superparticles of Co, Mn and Ni ferrite featured with comb-type and/or linear amphiphilic polyelectrolytes; NMR and MRI relaxometry

Abstract: The ability to encapsulate hydrophobic ferrites in colloidal superparticle structures of an a-telechelic hexadecyl-functionalized poly(methacrylic acid) (C16H33-PMAA) polymer with a linear architecture was investigated and compared with that of two amphiphilic comb-type water-soluble copolymers, namely, P(ANa-co-DAAm) and P(MANa-co-DMA), which are comprised of a poly(sodium acrylate) or poly(sodium methacrylate) backbone and pendent dodecyl acrylamide or dodecyl methacrylate chains, respectively. In the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(66 reference statements)
1
12
0
1
Order By: Relevance
“…Moreover, the difference between MnNCs and Mn@CoNCs stems from the different size of clusters (75 and 81 nm, respectively). Both clusters due to their size belong to the so-called motional average regime (MAR) where relaxivities increases in respect to the nanocluster diameter [46], as also indicated by us before [47].…”
Section: Preliminary Mri Studiessupporting
confidence: 60%
“…Moreover, the difference between MnNCs and Mn@CoNCs stems from the different size of clusters (75 and 81 nm, respectively). Both clusters due to their size belong to the so-called motional average regime (MAR) where relaxivities increases in respect to the nanocluster diameter [46], as also indicated by us before [47].…”
Section: Preliminary Mri Studiessupporting
confidence: 60%
“…Such small size could be related to the size of single crystal while TEM images revealed the particle dimension. However, slightly higher sizes could be optimal for the enhancement of the r 2 relaxivity [ 35 , 36 ]. In addition, the small-sized SPIONs increased the surface-to-volume ratio, and thus the increased dead layer component decreased magnetization ( M S ) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, MNPs smaller than 7 nm could not positively affect the r 2 relaxivity. However, slightly higher sizes could be optimal for the enhancement of the r 2 relaxivity [15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…r 2 / r 1 is an indicator of MRI efficiency that increases with the increment of field strength [13]. Some studies evaluated CoFe 2 O 4 MNPs as MR contrast agent in different sizes and various magnetic fields, confirming the above‐mentioned content [2, 14–17]. The studies indicated that high r 2 / r 1 was obtained in large sizes and high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%